An update on the pharmacogenetics of treating hypertension - Fontana, V.; Luizon, Marcelo Rizzatti [UNESP]; Sandrim, V. C. [UNESP] (Nature Publishing Group, 2015)
Hypertension is a leading cause of cardiovascular mortality, but only one third of patients achieve blood pressure goals despite antihypertensive therapy. Genetic polymorphisms may partially account for the interindividual variability and abnormal response to antihypertensive drugs. Candidate gene and genome-wide approaches have identified common genetic variants associated with response to antihypertensive drugs. However, there is no currently available pharmacogenetic test to guide hypertension treatment in clinical practice. In this review, we aimed to summarize the recent findings on pharmacogenetics of the most commonly used antihypertensive drugs in clinical practice, including diuretics, angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers, beta-blockers and calcium channel blockers. Notably, only a small percentage of the genetic variability on response to antihypertensive drugs has been explained, and the vast majority of the genetic variants associated with antihypertensives efficacy and toxicity remains to be identified. Despite some genetic variants with evidence of association with the variable response related to these most commonly used antihypertensive drug classes, further replication is needed to confirm these associations in different populations. Further studies on epigenetics and regulatory pathways involved in the responsiveness to antihypertensive drugs might provide a deeper understanding of the physiology of hypertension, which may favor the identification of new targets for hypertension treatment and genetic predictors of antihypertensive response.